2023
DOI: 10.1038/s41467-023-38700-5
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking complex soil systems as carbon sinks: multi-pool management as the key

Abstract: Much research focuses on increasing carbon storage in mineral-associated organic matter (MAOM), in which carbon may persist for centuries to millennia. However, MAOM-targeted management is insufficient because the formation pathways of persistent soil organic matter are diverse and vary with environmental conditions. Effective management must also consider particulate organic matter (POM). In many soils, there is potential for enlarging POM pools, POM can persist over long time scales, and POM can be a direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(32 citation statements)
references
References 129 publications
(161 reference statements)
0
16
0
Order By: Relevance
“…Nitrogen input can significantly alter soil carbon levels, but there is still controversy in long-term studies regarding changes in soil carbon accumulation associated with nitrogen addition. 43 Here, we report that A. dahurica var. formosana soil responded positively to nitrogen reduction in terms of carbon accumulation.…”
Section: ■ Discussionmentioning
confidence: 92%
“…Nitrogen input can significantly alter soil carbon levels, but there is still controversy in long-term studies regarding changes in soil carbon accumulation associated with nitrogen addition. 43 Here, we report that A. dahurica var. formosana soil responded positively to nitrogen reduction in terms of carbon accumulation.…”
Section: ■ Discussionmentioning
confidence: 92%
“…In addition, our results showed that microbial necromass C could be well predicted by microbial functional genes/pathways, indicating that microbial catabolism and anabolism play a critical role in mediating microbial necromass C. In this study, we found a higher microbial neromass C in the native‐vegetated coastal sediment. The microbial neromass C is the mineral‐associated organic matter (MAOM), which is an important component of stable C pool and may persist for centuries to millennia (Angst et al, 2023; Liang et al, 2019; Wang, An, et al, 2021). In addition to MAOM, particulate organic matter (POM) containing plant‐derived compounds is also a major part of stable C pool and may be precursors of MAOM with a short residence time (Angst et al, 2023; Lavallee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The microbial neromass C is the mineral‐associated organic matter (MAOM), which is an important component of stable C pool and may persist for centuries to millennia (Angst et al, 2023; Liang et al, 2019; Wang, An, et al, 2021). In addition to MAOM, particulate organic matter (POM) containing plant‐derived compounds is also a major part of stable C pool and may be precursors of MAOM with a short residence time (Angst et al, 2023; Lavallee et al, 2020). The efficient transformation of plant‐derived C into more persistent microbially derived C increase the contribution of microbial necromass to the stable C pool, which was reported to be influenced by plant diversity (Bai & Cotrufo, 2022; Prommer et al, 2020; Zhu et al, 2020) and management strategies (Hu et al, 2023; Zhou et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…How much of the depleted reservoir we could replenish will depend on the type of soil and climate, and on innovative technologies and management practices to sequester soil C (e.g. Angst et al., 2023).…”
Section: Discussionmentioning
confidence: 99%